THE EFFECT OF CONVERSION OF CONVENTIONAL BANKS TO ISLAMIC BANKS: EVIDENCE FROM GCC COUNTRIES (International Journal of Islamic Business, 2020)
The conversion from conventional to Islamic banking is one of the important topics in the Islamic finance industry due to non-existence of comprehensive framework for the conversion process contributing to several problems for the converted banks. Thus, the main purpose of this paper is to investigate the effect of conversion from conventional to Islamic banking on the converted banks’ operations. In addition, this paper will shed some light on the motivation behind the conversion and the process of conversion as well as providing answers to some of the problems that could hinder the conversion process. The analytical method used is ratio analysis (t-test) on the data extracted from BankScope database of five banks operating in the Gulf Cooperation Council (GCC) countries. The findings show that conversion helped to improve the performance and financial position of the converted banks, leading to sharp increases in assets, deposits, equity, and net income. Despite these benefits, however, the converted banks' profitability, efficiency, asset quality, liquidity, and risk indicators do not improve. This dichotomy may be due in part to the management’s inability to utilize the banks’ funds more efficiently to bring performance in line with increases in assets, deposits, equity, and net income. The findings indicate that the conversion methods play an important role in the conversion process because choosing the wrong method could slow or rescind the conversion. Thus, this study suggests that the conversion method and banks' management competencies must be taken into account prior to conversion.